2010
DOI: 10.1007/s10470-010-9557-6
|View full text |Cite
|
Sign up to set email alerts
|

A low-noise clockless simultaneous 32-channel wireless neural recording system with adjustable resolution

Abstract: We present a 32-channel wireless implantable neural recording (WINeR-5) system-on-a-chip (SoC) that operates based on time division multiplexing (TDM) of pulse width modulated (PWM) samples, similar to a singleslope analog to digital converter (ADC) that is made wireless. By transmitting a TDM-PWM signal, we have relaxed the need for wide bandwidth and accurate timing between transmitter and receiver units, which is necessary in wideband digital wireless links. The WINeR-5 system uses FSK modulation scheme wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…Such a wireless system must fulfill multiple stringent requirements for advancing neuroscience and the needs of clinical patients. Challenges include optimal ultralow-power circuit design, tight system integration, leak-proof device packaging, and compatibility with surgical implantation procedures [2][3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Such a wireless system must fulfill multiple stringent requirements for advancing neuroscience and the needs of clinical patients. Challenges include optimal ultralow-power circuit design, tight system integration, leak-proof device packaging, and compatibility with surgical implantation procedures [2][3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…We introduced a Wireless Integrated Neural Recording system (WINeR-5) in [6] as a substitute for hardwires in recording setups from freely moving animals in behavioral neuroscience research applications. This removes a source of motion artifacts and bias in the experimental results due to psychological effects of tethering.…”
mentioning
confidence: 99%
“…Neural signals are amplified and filtered by an array of capacitively coupled fully differential LNAs with adjustable gain (67.8/78dB) and bandwidth (HPF: 0.1Hz-1kHz/LPF: 8kHz) [6]. Our prior experience with WINeR-5 showed that although each LNA consumes a small current (∼25μA), since there are 32 of them, the LNA block quickly becomes the dominant power consumer (42%).…”
mentioning
confidence: 99%
“…Several research groups have implemented active back-telemetry links for neural recording systems using commercial components (Obeid et al, 2003;Hawley et al, 2002, Gosalia et al, 2004 or custom ASICs (Lee et al, 2010;Yin and Ghovanloo, 2011;Chae et al, 2009;Miranda et al, 2010;Rizk et al, 2009;Mohseni and Najafi, 2004). In most of these designs the IMD Tx is significantly simplified to reduce the size and power consumption at the expense of more complexity in the external Rx.…”
Section: Backward Telemetrymentioning
confidence: 99%
“…A key limitation of the current wireless neural recording systems that are developed for neuroscience applications is the need for the animal subject to carry a large payload of batteries for continuous recording over several hours or even days (Lee et al, 2010;Yin and Ghovanloo, 2011;Chae et al, 2009). This may not be a major issue for larger animal subjects such as non-human primates (Gao et al, 2012;Rizk et al, 2009).…”
Section: Introductionmentioning
confidence: 99%